Profitability of Non-Timber Forest Products (NTFPS) Production and Marketing in Zuru Local Government Area, Kebbi State: A Case for Honey - A. A, Senchi; Malami, A. A (International Journal of Sustainable Agricultural Research, 2015)
The study examined production and marketing of honey in Zuru Local Government area of Kebbi state. This research covers five district areas of Dabai, Manga, RafinZuru, Rikoto and Senchi. Five villages each of the districts were purposively selected, four (4) respondents were randomly selected from each village giving a total sample size of 100 respondents. 100 structured and open – ended questionnaires were administered, out of this number, 86 were retrieved. The data were analyzed using simple descriptive statistics and gross margin. In the marketing channels, individual consumers are the most active patronizers whereabout 36.0 and 37.2% of the honey producers and marketers respectively obtained between N6001 – N8000 and N2801 - N4800 net profit per week. The total profit made by the producers and marketers of honey were ₦610,150.00 and ₦478,560.00, while the average profits were ₦7,094.77 and ₦5,564.65 per week. Thus, honey production and marketing is a profitable business in the area. The rate of return was 375.93. The benefit cost ratio is greater than one (4.76), indicating that revenue from the business is able to cover the total cost. To address the problem of capital, the study recommended that honey producers and marketers should form co-operative societies so as to enable them access loans to boost their business.